2017
DOI: 10.7554/elife.27601
|View full text |Cite|
|
Sign up to set email alerts
|

Type III CRISPR-Cas systems can provide redundancy to counteract viral escape from type I systems

Abstract: CRISPR-Cas-mediated defense utilizes information stored as spacers in CRISPR arrays to defend against genetic invaders. We define the mode of target interference and role in antiviral defense for two CRISPR-Cas systems in Marinomonas mediterranea. One system (type I-F) targets DNA. A second system (type III-B) is broadly capable of acquiring spacers in either orientation from RNA and DNA, and exhibits transcription-dependent DNA interference. Examining resistance to phages isolated from Mediterranean seagrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 59 publications
10
78
4
Order By: Relevance
“…This arrangement provides the subtype VI-B array with an abundance of nonfunctional spacers and unnecessary carry-over of PAM sequences but spares it the cost of maintaining an adaptation module. The capability to utilize other adaptation modules enforces the concept of modularity in CRISPR-Cas systems that has so far been experimentally shown on the 290 interference level of the immune response (46)(47)(48). We complement these findings with the first case of demonstrated inter-type CRISPR adaptation and also highlight F. columnare as one of the few species (49) that can be natively induced to acquire spacers from lytic phages in laboratory conditions.…”
Section: Discussionsupporting
confidence: 58%
“…This arrangement provides the subtype VI-B array with an abundance of nonfunctional spacers and unnecessary carry-over of PAM sequences but spares it the cost of maintaining an adaptation module. The capability to utilize other adaptation modules enforces the concept of modularity in CRISPR-Cas systems that has so far been experimentally shown on the 290 interference level of the immune response (46)(47)(48). We complement these findings with the first case of demonstrated inter-type CRISPR adaptation and also highlight F. columnare as one of the few species (49) that can be natively induced to acquire spacers from lytic phages in laboratory conditions.…”
Section: Discussionsupporting
confidence: 58%
“…This mechanism can lead to cell death or dormancy when high levels of target mRNA are detected or when the target is mutated. As such, type III systems have been proposed to form a second line of defence able to block phage infection when type I systems fail 21 . It should be noted that this experimentally verified interaction between systems is based on two cas clusters that are not in a single locus.…”
Section: Discussionmentioning
confidence: 99%
“…There, it was found that the type III-B system can use crRNAs from the type I-F system, enabling the same guide RNA to target phages with different interference modules. These different Cas interference complexes have diverse molecular requirements, thus limiting the emergence of phages escape mutants 21 . Many cas genes are found near CRISPRs, but distant arrays (i.e., CRISPRs without neighboring cas genes) have also been identified 8,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Diverse cas genes may allow hosts to evade the action of these 442 anti-CRISPR proteins, which are often extremely broadly acting [53,54]. Alternatively, 443 it has recently been shown that promiscuous type III Cas proteins are often encoded 444 alongside type I systems and can function as a "backup", using spacers from the same 445 12/18 array to target phages that have mutated the protospacer-adjacent motifs necessary for 446 type I targeting [56]. Most genomes with multiple cas signature genes also had multiple 447 types of such genes, suggesting some diversifying force.…”
mentioning
confidence: 99%